2019
DOI: 10.1097/ncc.0000000000000697
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Chinese-Version Normalization Assessment Measure for Primary Caregivers of Children With Cancer

Abstract: Background “Normalization” refers to the process whereby a household with a chronically ill member returns to a normal life to reduce its distress. There has been no valid and reliable instrument to investigate such normalization in Taiwan. Objective The aims of this study were to develop and validate a Chinese version of the Normalization Assessment Measure for Caregivers of Children With Cancer (NAM-CCC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Parents are expected to adjust to the various changes within their families' structure. It is commonly observed that families with cancer children aspire for normalcy in their daily lives [11].…”
Section: Participants and Settingmentioning
confidence: 99%
“…Parents are expected to adjust to the various changes within their families' structure. It is commonly observed that families with cancer children aspire for normalcy in their daily lives [11].…”
Section: Participants and Settingmentioning
confidence: 99%